Pengaruh Pemahaman Akuntansi UMKM Terhadap Minat Mahasiswa Akuntansi dalam Mendukung Ekonomi Kerakyatan - Sayekti, Fitria; Baroroh, Kiromim (Indonesian Journal Publisher, 2025)
This study aims to analyze the influence of MSME accounting understanding on accounting students' interest in supporting a people-centered economy. A quantitative approach was used, using a survey method of 184 undergraduate accounting students at Yogyakarta State University who had taken MSME accounting and people-centered economy courses. Data were analyzed using multiple linear regression. The results indicate that basic accounting knowledge, involvement in people-centered economic activities, and knowledge of people-centered economic principles have a positive and significant effect on the application of people-centered economic principles to MSMEs. Meanwhile, practical skills and entrepreneurial interest did not have a significant effect. The R² value of 0.727 indicates the model's ability to explain the strong relationship between the variables. These findings underscore the importance of strengthening an applicable accounting curriculum and collaboration between universities and MSMEs in preparing students to play an active role in developing a people-centered economy in Indonesia.